2015
DOI: 10.1016/j.catena.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal and pollen analysis: Examples of Holocene fire dynamics in Mediterranean Iberian Peninsula

Abstract: ResumenEl fuego juega un papel esencial en la configuración de los paisajes vegetales, aunque nuestro conocimiento de su incidencia a lo largo del tiempo es muy fragmentario y suele basarse en un escaso número de fuentes. Con objeto de indagar las limitaciones y complementariedad de éstas, se confrontan los resultados de algunas técnicas analíticas (estudio de los carbones sedimentarios y de suelo, del polen, del levoglucosán, de isótopos de plomo y de metales pesados presentes en las turberas para periodos qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 89 publications
1
28
0
Order By: Relevance
“…Numerous local and regional studies have clearly demonstrated that the activity of long‐term fires in the Mediterranean basin follows specific activity patterns (Colombaroli et al, ; Turner et al, ; Vannière et al, , ; Gil‐Romera et al, ; Leys et al, ; Burjachs & Expósito, ). Such research provides solid evidence on synchronous trends usually interpreted as climatically driven but also documents unforeseen ecosystem behaviors in response to particular physical configurations, vegetation, and anthropic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous local and regional studies have clearly demonstrated that the activity of long‐term fires in the Mediterranean basin follows specific activity patterns (Colombaroli et al, ; Turner et al, ; Vannière et al, , ; Gil‐Romera et al, ; Leys et al, ; Burjachs & Expósito, ). Such research provides solid evidence on synchronous trends usually interpreted as climatically driven but also documents unforeseen ecosystem behaviors in response to particular physical configurations, vegetation, and anthropic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, the incidence of human‐induced fires on the frequency, fire regime, and biomass burning is still an open issue in Iberia (Carrión et al, ; Bal et al, ; Bowman et al, ; Morales‐Molino et al, ). Most paleofire studies have reconstructed fire history (e.g., Abel‐Schaad et al, , ; López‐Merino et al, ; López‐Sáez et al, , , ; Abel‐Schaad & López‐Sáez, ; Morales‐Molino et al, ; Burjachs & Expósito, ; Silva‐Sánchez et al, ; Morales‐Molino et al, ) and in certain cases fire regime (e.g., Bal et al, ; Gil‐Romera et al, ; Morales‐Molino et al, ), but only a few have taken into account regional variability on a spatial scale discerning discrepancies or agreement among records (Gil‐Romera et al, ; Vannière et al, ; López‐Sáez et al, ; Morales‐Molino et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires are a recurrent threat in the Mediterranean region since the Holocene (Burjachs & Expósito, ), with the burned area in the Iberian Peninsula averaging more than 100,000 ha every year during the last decade (San‐Miguel‐Ayanz et al, ). Wildfires play a major role on land degradation in Mediterranean areas (Le Houérou, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fire signal and pollen data facilitate an understanding of historical disturbances in the landscape (Burjachs & Expósito, ; González‐Pellejero, Allende, López‐Sáez, Frochoso‐Sánchez, & Alba‐Sánchez, Abel‐Schaad, ). As Conedera et al () report, the creation of effective land management approaches requires a sound understanding of past forest stands and of landscape dynamics.…”
Section: Introductionmentioning
confidence: 99%